Sex Differences and Similarities in Atrial Fibrillation Epidemiology, Risk Factors and Mortality in Community Cohorts: Results from the BiomarCaRE Consortium - Magnussen, Christina (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a common cardiac disease in aging populations with high comorbidity and mortality. Sex differences in AF epidemiology are insufficiently understood. METHODS: In N=79,793 individuals without AF diagnosis at baseline (median age 49.6 years, age range 24.1-97.6 years, 51.7% women) from four community-based European studies (FINRISK, DanMONICA, Moli-sani, Northern Sweden) of the BiomarCaRE consortium, we examined AF incidence, its association with mortality, common risk factors, biomarkers and prevalent cardiovascular disease, and their attributable risk by sex. Median follow-up time was 12.6 (to a maximum of 28.2) years. RESULTS: Fewer AF cases were observed in women, N=1,796 (4.4%) than in men, N=2,465 (6.4%). Cardiovascular risk factor distribution and lipid profile at baseline were less beneficial in men compared to women and cardiovascular disease was more prevalent in men. Cumulative incidence increased markedly after the age of 50 years in men and after 60 years in women. The lifetime risk was similar (more than 30%) for both sexes. Subjects with incident AF had a 3.5-fold risk of death compared to those without AF. Multivariable-adjusted models showed sex differences for the association of body mass index (BMI) and AF, hazard ratio (HR) per standard deviation (SD) increase 1.18, 95% confidence interval (CI) 1.12 to 1.23 in women versus 1.31, 95% CI 1.25 to 1.38 in men; interaction P value 0.001. Total cholesterol was inversely associated with incident AF with a greater risk reduction in women, HR per SD 0.86, 95% CI 0.81 to 0.90 versus 0.92, 95% CI 0.88 to 0.97 in men, interaction P value 0.023. No sex differences were seen for C-reactive protein and N-terminal pro B-type natriuretic peptide. The population attributable risk of all risk factors combined was 41.9% in women and 46.0% in men. About 20% of the risk was observed for BMI. CONCLUSIONS: Lifetime risk of AF was high and AF was strongly associated with increased mortality both in women and men. BMI explained the largest proportion of AF risk. Observed sex differences in the association of BMI and total cholesterol with AF need to be evaluated for underlying pathophysiology and relevance to sex-specific prevention strategies.